Socio-demographic characteristics and associated factors influencing cervical cancer screening among women attending in St. Paul’s Teaching and Referral Hospital, Ethiopia - Abebe Belete Woldetsadik; Abebe Feyissa Amhare; Sintayehu Tsegaye Bitew; Leilei Pei; Jian Lei; Jing Han (BMC Women's Health, 2020)
Abstract Background In Ethiopia, cervical cancer is the second most frequent cancer among women aged 15 to 44 years old. Cervical cancer screening is an effective measure to enhance the early detection of cervical cancer for prevention. However, the magnitude of cervical cancer screening is less than 1%. This study aimed to determine the influence of sociodemographic characteristics and related factors on screening. Method A hospital-based cross-sectional study has been conducted from July to September 2017. Data have been collected using interviewer-administered questioner among 425 women (18–49 years age) who visited the family health department at St. Paul’s Hospital. Descriptive statistics, chi-square, univariate and multivariate logistic regression were used for data analysis. Result Of the 425 study participants, only 12.2% of women have been screened within the past 3 years. Women in the age range of 40–49 years old were more likely to be screened (36.1%) than women age 18–29 years (8%). Women living in urban were more likely to be screened (15.9%) than women living in rural (3.9%). Other factors including low monthly income, unlikely chance of having cancer, lack of knowledge, and fear test outcome were significantly associated with the low uptake of screening. Conclusion This study revealed that the uptake of cervical cancer screening was low. Women in the potential target population of cervical cancer screening were just a proportion of all studied age groups and screening in them was more common than in younger women. Besides, rural residence, low monthly income, and lack of knowledge were important predictors for low utilization of cervical cancer screening practice.